The Role of Freeze-Drying as a Multifunctional Process in Improving the Properties of Hydrogels for Medical Use - Kacper Odziomek; Anna K. Drabczyk; Paulina Kościelniak; Patryk Konieczny; Mateusz Barczewski; Katarzyna Bialik-Wąs (Pharmaceuticals)
Background/Objectives: Freeze-drying is a dehydration method that extends the shelf life and stability of drugs, vaccines, and biologics. Recently, its role has expanded beyond preservation to improve novel pharmaceuticals and their carriers, such as hydrogels, which are widely studied for both drug delivery and wound healing. The main aim of this study was to explore the multifunctional role of freeze-drying in improving the physicochemical properties of sodium alginate/poly(vinyl alcohol)-based hydrogels for medical applications. Methods: The base matrix and hydrogels containing a nanocarrier-drug system, were prepared by chemical cross-linking and then freeze-dried for 24 h at −53 °C under 0.2 mBa. Key analyses included determination of gel fraction, swelling ratio, FT-IR, SEM, TG/DTG, in vitro drug release and kinetics, and cytotoxicity assessment. Results: Freeze-drying caused an increase in the gel fraction of the hydrogel with the dual drug delivery system from 55 ± 1.6% to 72 ± 0.5%. Swelling ability was pH-dependent and remained in the same range (175–282%). Thermogravimetric analysis showed that freeze-dried hydrogels exhibited higher thermal stability than their non-freeze-dried equivalents. The temperature at 10% weight loss increased from 194.0 °C to 198.9 °C for the freeze-dried drug-loaded matrix, and from 188.4 °C to 203.1 °C for the freeze-dried drug-free matrix. The average pore size of the freeze-dried hydrogels was in the range of 1.07 µm ± 0.54 to 1.74 µm ± 0.92. In vitro drug release revealed that active substances were released in a controlled and prolonged way, according to the Korsmeyer–Peppas model. The cumulative amount of salicylic acid released at pH = 9.0 after 96 h was 63%, while that of fluocinolone acetonide reached 73%. Both hydrogels were non-toxic to human fibroblast cells, maintaining over 90% cell viability after 48 h of incubation. Conclusions: The results show a high potential for commercialisation of the obtained hydrogels as medical dressings.